Case report on trial: Do you, Doctor, swear to tell the truth, the whole truth and nothing but the truth? - Yitschaky, Oded (BioMed Central, 2011)
We are in the era of "evidence based medicine" in which our knowledge is stratified from top to bottom in a hierarchy of evidence. Many in the medical and dental communities highly value randomized clinical trials as the gold standard of care and undervalue clinical reports. The aim of this editorial is to emphasize the benefits of case reports in dental and oral medicine, and encourage those of us who write and read them.